Sustainability and substitution of exhaustible natural resources. How resource prices affect long-term R&D-investments - Lucas Bretschger; Sjak Smulders (ETH Zurich, CER-ETH - Center of Economic Research, 2006)
Traditional resource economics has been criticised for assuming too high elasticities of substitution, not observing material balance principles and relying too much on planner solutions to obtain long-term growth. By analysing a multi-sector R&Dbased endogenous growth model with exhaustible natural resources, labour, and knowledge capital as inputs, the present paper addresses this critique. We study transitional dynamics and the long-term growth path and identify conditions under which firms keep spending on research and development so that growth is sustained. We demonstrate that long-run growth can be sustained under free market conditions even when elasticities of substitution between man-made inputs and resources are low.
Keywords: Q20; Q30; O41; O33; 330; Growth; non-renewable resources; substitution; investment incentives; endogenous technological change; sustainability; Erschöpfbare Ressourcen; Nachhaltige Entwicklung; Endogenes Wachstumsmodell; Ressourcenökonomik; Theorie